(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
The rapid proliferation of drones in the United States has created urgent challenges concerning individual privacy, institutional readiness, and legal enforcement. While drones serve diverse functions, their use in surveilling private spaces without consent has exposed significant regulatory gaps in both federal and local legal frameworks. This research investigates these gaps by analyzing a real-life case from Silicon Valley, where a civilian encountered a drone hovering above their private residence and was unable to obtain meaningful assistance from law enforcement.Drawing on recent scholarship, including Siddiqui and Muniza’s “Regulatory Gaps in Drone Surveillance” [Annals of Human and Social Sciences, 2025] and “The Drone’s Gaze: Religious Perspectives on Privacy and Human Dignity” [Al-Qamar, 2024], this paper reveals how current laws fail to protect against aerial intrusions, especially in residential zones. The findings are further contextualized within broader institutional weaknesses, as previously identified in “Public Funds, Private Gains” [JARSSH, 2022] and “Hybrid Warfare and the Global Threat of Data Surveillance” [PSSR, 2025].Moreover, the paper critiques recent legislative efforts, such as the U.S. Countering CCP Drones Act (H.R.2864), through the lens of Siddiqui and Muniza’s (2025) analysis published in the Social Sciences & Humanity Research Review, and assesses their ineffectiveness against AIpowered foreign-manufactured surveillance drones. Philosophical and constitutional dimensions are explored through works like “Liberalism in South Asia” [CIBGP, 2008], and “Constitutional Vulnerability in the Age of Digital Surveillance” [CRLSJ, 2025] The research proposes a three-pronged regulatory framework: 1. Modernization of legal statutes to close regulatory and constitutional loopholes; 2. Institutional upskilling through integrated AI-based geofencing and centralized FAADHS-local reporting platforms; 3. Public empowerment via education, civic engagement, and participatory complaint channels. The paper concludes that safeguarding privacy and national security in the drone era requires an interdisciplinary approach—bridging law, technology, ethics, and public participation. Only through such coordinated efforts can drone innovation be directed toward public benefit without compromising civil liberties.